Prevalencia de sarcocystis (sarcocystis camely) en camelidos sudamericanos, en el centro de rastro del canton Saquisili. - Gómez Rodríguez, María Fernanda (2022)
The present research project is based on the macroscopic and microscopic identification of Sarcocystis spp. in situ in the slaughter center of the Saquisili canton, in addition to quantify the prevalence of Sarcosporidiosis according to gender in the periods from 2019 to 2022 in the slaughter center mentioned above and propose sanitary measures to prevent, control and eradicate Sarcocystis spp. in alpaca producers in the area and in the country. in alpaca producers in the area and in the country, adult alpacas older than 3 years of age have a higher percentage of Sarcocystis spp infection than young alpacas and in the summer season there is a higher percentage of infection in alpacas compared to the winter season with a higher probability of presenting Sarcocystis spp cysts and oocysts, representing a risk factor for biosecurity. The prevalence of infection and factors associated with the presence of Sarcocystis spp in slaughtered alpacas in the Saquisili herd is important for the reason that diagnoses of the diseases that affect these species are not performed and it is essential to carry out both assistance and permanent sanitary controls to improve the management and breeding of the herds. Sarcocystis spp. is a zoonotic parasitic disease that is important to manage in order to protect human wel-being. The slaughterhouse of Saquisili is located by way of Canchagua. Total area of the square: 3,640.24 m2, where this observational research was conducted, allowing to collect information to establish the prevalence of Sarcocystis spp in South American camelids slaughtered at the slaughterhouse of Saquisili in order to be able to obtain a sanitary status of the carcasses of these animals, obtaining the following results in the month of May 2019 there was a prevalence of Sarcocystis spp. parasite, in the years 2020 and 2021 there was no prevalence due to the pandemic situation and in the present year 2022, in the month of July there was a prevalence of the parasite. The conclusion reached is that the prevalence of Sarcocystis spp. is minimal in the slaughter center of the Saquisili canton.